Quality assessment of different brands of atorvastatin tablets available in Riyadh, Saudi Arabia - Ali AlMuhsin; Abdul Ahad; Yousef A. Bin Jardan; Mohammad Raish; Ajaz Ahmad; Khalid M. Alkharfy; Fahad I. Al-Jenoobi (BMC, 2022)
Abstract Background Hypolipidemic agents have been shown to be helpful in the primary and secondary prevention of cardiovascular disease. Most often, statins are prescribed to treat hyperlipidemia. There are a number of statins available in the market today, but atorvastatin is the most widely prescribed. It is essential that the drugs should have the appropriate amount of active pharmaceutical ingredient and meet the necessary physical properties. The main purpose of the study was to evaluate the quality of different marketed brands of atorvastatin calcium tablets available in Saudi Arabia. Methods In this study, innovator product coded as (AS-1) and five generics brands (coded as AS-2 to AS-6) of atorvastatin tablets 20 mg available in Saudi Arabia were evaluated for in vitro dissolution test, weight variations, friability and hardness tests. The analysis of drug was carried out by "high-performance liquid chromatography" (HPLC) method using C18 column (4.6 × 150 mm, 5 μm). The mobile phase was consisted of acetonitrile and HPLC water (pH 2.1, adjusted with orthophosphoric acid) in ratio of 52:48 v/v, the flow rate was 1.0 ml/min. Atorvastatin was detected at a wavelength of 254 nm. Results According to the results of the dissolution study, the investigated products released more than 90% of atorvastatin in 15 min. Within 60 min, the brands AS-1, AS-3, AS-5, and AS-6 depicted nearly 100% atorvastatin release, while the brand AS-2 displayed 91.69% drug release. According to our findings, the investigated atorvastatin innovator (AS-1) and generic brands such as AS-2 to AS-6 were of good pharmaceutical quality. Conclusions All generic brands of atorvastatin tablets available in the Saudi Arabian market met the pharmacopoeia's consistency checks such as weight variation, friability, hardness and in vitro dissolution. Hence, focusing on their in vitro release properties, it was determined that these brands could be used interchangeably.